(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This journal investigates the contextual learning through Live-In activities in empowering students at Homeschooling Primagama Semarang. Contextual learning integrates academic knowledge with practical experiences in real-world settings, with Live-In activities involving students residing in rural areas, interacting with local communities, and participating in cultural and practical activities. The study’s objective is to evaluate the impact of Live-In activities on students’ personal, social, and academic development. The research methodology employs qualitative analysis, including observations, and interviews to examine students’ experiences during Live-In activities, aiming to identify patterns and themes related to student empowerment. The study reveals that contextual learning through Live-In activities has a positive influence on students. They acquire social skills, responsibility, empathy, independence, and actively engage in learning. Furthermore, students gain a deeper understanding of ethics, culture, and social diversity. The empowerment process encompasses intrapersonal, interactional, and participatory aspects, fostering self-awareness, enhanced life skills, and improved ability to interact with their environment. In conclusion, contextual learning through Live-In activities proves to be an effective approach for empowering students at Homeschooling Primagama Semarang. To maximize the benefits of this method, it is recommended to specify empowerment objectives in activity proposals, refine student assessments, and enhance the clarity of activity objectives for teachers